Analysis on Students Perception of English Reading Anxiety at Grade XI of SMA Negeri 1 Aek Songsongan Academic Year 2021/2022 - Widia Sani Hasibuan; Zulfitri (Medan Resource Center, 2022)
Most students of English Education of UMN Al Washliyah faced many difficulties to communicate in English. Their lack of confidence was because students’anxiety which affecting students reading skill. The objective of this reseach was to investigate the factors affecting students’ anxiety in reading skill. The Qualitative Research Method was used in this research.The subjects of this research chosen were 6 students as the representative of students in the eleventh grade MIPA 1 of SMA Negeri 1 Aek Songsongan academic year 2021-202. Technique of collecting data used the interview in which the students were interviewed after finishing reading test. Reading in the class was the dominant indicator foundon the students’ anxiety because they did not feel confidence to read in the class. Negative background experience, unfamiliar cultures, and fear of making mistake and apprehension about other evaluation were the indicators which more seldom foundbecause the condition was not formal. Moreover, all the data showed that students who were higher in reading ability got the lower score, students who were moderate in reading got moderate score, and students who were lower in reading got higher score. Shortly, this finding of the research was appropriate with the assumption in this research that was the higher students’ anxiety the lower their reading skill and the lower students’ anxiety the higher their reading skill